Corrigendum to “Recent Development in Ammonia Stripping Process for Industrial Wastewater Treatment” - Kinidi, Lennevey; Shanti Faridah, Salleh; Noraziah, Abdul Wahab; Khairul Fikri, Tamrin; Hipolito, Cirilo Nolasco; Ivy Tan, Ai Wei (Hindawi, 2019)
In the article titled “Recent Development in Ammonia Stripping Process for Industrial Wastewater Treatment” [1], the order of the authors was incorrect. In addition, the name of the second author was given incorrectly as Shanti Faridah Salleh. &e author’s name should have been written as S. F. Salleh. &e revised authors’ list is shown above.